Hodgkin’s Lymphoma: A Rare Ophthalmic Case Report - Kadir, Syeed Mehbub Ul; Hossain, Tanjilla; Haider, Md Golam (Community Based Medical Journal, 2022)
Hodgkin’s lymphoma (HL) is a disease originating from lymphoid tissues; however, it may pose a diagnostic challenge. Ocular involvement is more prevalent in non-HL compared to HL. We have reported a rare case of Hodgkin’s lymphoma presented with forwarding bulging of left eye with pain, redness, and watering. The patient also complained of painless swelling of the submandibular lymph node when admitted into the National Institute of Ophthalmology and Hospital (NIOH), Dhaka, Bangladesh; later, incision and biopsy was done at ENT & Head-Neck Cancer Hospital, Dhaka, Bangladesh. Histopathology report revealed Hodgkin’s lymphoma. Hodgkin's lymphoma is a malignancy with unknown aetiology. With timely diagnosis and early treatment, our patient began to show gradual improvement with her symptoms. Prompt oncologic treatment and immunotherapy can be beneficial, if instituted early in the course of the disease. CBMJ 2022 July: vol. 11 no. 02 P: 158-161